The Implementation of the Suggestopedia Method in Reading Comprehension Skills for Fourth Grade Elementary School Students - Elsya Nadia; Dina Mardiana; Ichyatul Afrom; Wahyu Nugroho (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Background: The Suggestopedia method is a learning approach that emphasizes providing positive suggestions to students through a comfortable, relaxed, and enjoyable learning environment. This method was developed by incorporating music, voice intonation, and a conducive classroom atmosphere to enhance students' concentration and their ability to absorb learning materials. Through this approach, the Suggestopedia method is believed to help students learn more effectively, particularly in improving their reading comprehension skills. Aim: This study aims to describe the implementation of the Suggestopedia method in instructional materials to improve the reading comprehension skills of fourth-grade elementary school students. The research employed a library research method using a qualitative descriptive approach with content analysis techniques. The data were collected from various relevant literature sources, including books, scientific journals, and previous research findings. The data collection technique involved document analysis of curriculum content standards for Indonesian language learning in elementary schools (SD/MI), theories of the Suggestopedia method, and the focus of Indonesian language learning materials for fourth-grade students. Result and Discussions: The findings revealed that six chapters in the fourth-grade Indonesian language curriculum are relevant for the implementation of the Suggestopedia method. These chapters include: Chapter 1 Fictional Stories and Life Values; Chapter 2 Understanding Nonfiction Texts; Chapter 3 Appreciating Children's Poetry; Chapter 4 Informative Texts (Facts and Opinions); Chapter 5 Simple Explanatory Texts; and Chapter 6 Indonesian Folktales. These six chapters are described according to the three stages of the Suggestopedia learning procedure proposed by Georgi Lozanov, as cited in Tarigan (2011), namely: the pre-session stage, the concert session stage, and the elaboration/active session stage.